2020
DOI: 10.1002/bit.27299
|View full text |Cite
|
Sign up to set email alerts
|

Limited life cycle and cost assessment for the bioconversion of lignin‐derived aromatics into adipic acid

Abstract: Lignin is an abundant and heterogeneous waste byproduct of the cellulosic industry, which has the potential of being transformed into valuable biochemicals via microbial fermentation. In this study, we applied a fast‐pyrolysis process using softwood lignin resulting in a two‐phase bio‐oil containing monomeric and oligomeric aromatics without syringol. We demonstrated that an additional hydrodeoxygenation step within the process leads to an enhanced thermochemical conversion of guaiacol into catechol and phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…6 . A recent limited life cycle assessment concluded the feasibility of the bio-based production of adipic acid from softwood lignin-derived aromatics based on P. putida as the whole-cell biocatalyst (van Duuren et al 2020 ) and even possible offset credits were promoted for the bioethanol biorefinery, if the lignin in the their wastewater is no longer burnt but converted to the value-added product adipic acid instead (Corona et al 2018 ). Purification of MA produced by P. putida from lignin model compounds by activated carbon treatment was demonstrated with a good recovery at > 97% purity.…”
Section: Bioproduction and Industrial Applicationmentioning
confidence: 99%
“…6 . A recent limited life cycle assessment concluded the feasibility of the bio-based production of adipic acid from softwood lignin-derived aromatics based on P. putida as the whole-cell biocatalyst (van Duuren et al 2020 ) and even possible offset credits were promoted for the bioethanol biorefinery, if the lignin in the their wastewater is no longer burnt but converted to the value-added product adipic acid instead (Corona et al 2018 ). Purification of MA produced by P. putida from lignin model compounds by activated carbon treatment was demonstrated with a good recovery at > 97% purity.…”
Section: Bioproduction and Industrial Applicationmentioning
confidence: 99%
“…Ideally, lignin conversion would reduce environmental impacts by saving energy in comparison with conventional petroleum-based products. Recently, an LCA for the production of lignin-derived adipic acid and catechol showed that it produces less CO 2 emissions and byproducts [166][167][168]. Most LCAs performed to data have concluded that lignin-based products offer better environmental performance than petroleum-based products due to their reduced impact in terms of climate change.…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
“…Valorization of lignin monomers directly into adipic acid is therefore an important challenge in chemical and synthetic biology. 2,6 Herein we report the synthesis of adipic acid from catechol (benzene-1,2-diol) and guaiacol (2-methoxyphenol) using engineered whole-cells of E. coli (Figure 1C). The one-pot reaction proceeds under mild conditions (37 ˚C, pH 7.2, aqueous media), requires no additives and produces no by-products.…”
Section: Take Down Policymentioning
confidence: 99%
“…To best of our knowledge, this is the first synthesis of adipic acid from guaiacol in an engineered microorganism. [5][6]18 Although the precise reason(s) for this latter increase in yield are currently unclear, the accumulation of ccMA and guaiacol in low-and high-OD reactions, respectively, indicates that a fine balance exists between GcoAB and BcER expression and activity in this pathway (Table S7).…”
Section: The Reaction B) Analysis Of Lyophilized Culture Supernatant By 1 H Nmr C)mentioning
confidence: 99%